Hospital case volume and outcomes for proximal femoral fractures in the USA: an observational study. Issue 4 (7th April 2016) - Metcalfe, David; Salim, Ali; Olufajo, Olubode; Gabbe, Belinda; Zogg, Cheryl; Harris, Mitchel B; Perry, Daniel C; Costa, Matthew L
Abstract : Objective: To explore whether older adults with isolated hip fractures benefit from treatment in high-volume hospitals. Design: Population-based observational study. Setting: All acute hospitals in California, USA. Participants: All individuals aged ≥65 that underwent an operation for an isolated hip fracture in California between 2007 and 2011. Patients transferred between hospitals were excluded. Primary and secondary outcomes: Quality indicators (time to surgery) and patient outcomes (length of stay, in-hospital mortality, unplanned 30-day readmission, and selected complications). Results: 91 401 individuals satisfied the inclusion criteria. Time to operation and length of stay were significantly prolonged in low-volume hospitals, by 1.96 (95% CI 1.20 to 2.73) and 0.70 (0.38 to 1.03) days, respectively. However, there were no differences in clinical outcomes, including in-hospital mortality, 30-day re-admission, and rates of pneumonia, pressure ulcers, and venous thromboembolism. Conclusions: These data suggest that there is no patient safety imperative to limit hip fracture care to high-volume hospitals.